Measurement and research using the Big Five, HEXACO, and narrow traits: A primer for researchers and practitioners - Jeromy Anglim; Peter O’connor (Australian Journal of Psychology, 2019)
Objective Personality traits influence human behaviour across a broad range of situations and are consequently relevant to many theoretical and applied disciplines. In this perspective piece, we provide an overview of the logic underpinning personality measurement and review major personality taxonomies. We provide an extensive set of recommendations for researchers and practitioners on when and how to use measures of personality traits. Method We overview a range of taxonomic representations of personality structure focusing particularly on hierarchical representations and five and six factor models such as the Big Five and HEXACO models. We review the various strengths and weaknesses of each approach. Results The review outlines the major reasons for the dominance of the Big Five model, and suggests it is a good descriptive framework for studying personality in general. However we suggest that researchers and practitioners also consider alternative taxonomic personality representations such as the HEXACO. We provide a range of scenarios whereby alternative frameworks will be more appropriate than the Big Five and offer recommendations both for choosing measures in general and for implementing studies examining personality facets. Conclusion Whilst the Big Five represents an excellent general personality framework that is appropriate across multiple situations, researchers and practitioners should be aware of alternative measures and utilise them where appropriate.